Direct Free Carrier Photogeneration in Single Layer and Stacked Organic Photovoltaic Devices. Issue 22 (3rd April 2017) - Chandran, Hrisheekesh Thachoth; Ng, Tsz‐Wai; Foo, Yishu; Li, Ho‐Wa; Qing, Jian; Liu, Xiao‐Ke; Chan, Chiu‐Yee; Wong, Fu‐Lung; Zapien, Juan Antonio; Tsang, Sai‐Wing; Lo, Ming‐Fai; Lee, Chun‐Sing
Abstract : High performance organic photovoltaic devices typically rely on type‐II P/N junctions for assisting exciton dissociation. Heremans and co‐workers recently reported a high efficiency device with a third organic layer which is spatially separated from the active P/N junction; but still contributes to the carrier generation by passing its energy to the P/N junction via a long‐range exciton energy transfer mechanism. In this study the authors show that there is an additional mechanism contributing to the high efficiency. Some bipolar materials (e.g., subnaphthalocyanine chloride (SubNc) and subphthalocyanine chloride (SubPc)) are observed to generate free carriers much more effectively than typical organic semiconductors upon photoexcitation. Single‐layer devices with SubNc or SubPc sandwiched between two electrodes can give power conversion efficiencies 30 times higher than those of reported single‐layer devices. In addition, internal quantum efficiencies (IQEs) of bilayer devices with opposite stacking sequences (i.e., SubNc/SubPc vs SubPc/SubNc) are found to be the sum of IQEs of single layer devices. These results confirm that SubNc and SubPc can directly generate free carriers upon photoexcitation without assistance from a P/N junction. These allow them to be stacked onto each other with reversible sequence or simply stacking onto another P/N junction and contribute to the photocarrier generation. Abstract : Subnaphthalocyanine chloride (SubNc) and subphthalocyanine chloride (SubPc) are identified as novel bipolar organic semiconductors with unusually high freecarrier generation upon photoexcitation. Functioning of devices with opposite stacking order (SubNc/SubPc vs SubPc/SubNc) confirms their operation does not rely on charge dissociation at the interfaces. These enable a new class of organic photovoltaic devices with non‐p–n‐junction‐based architectures.